Climate‐induced resource bottlenecks exacerbate species vulnerability: a review. Issue 7 (18th May 2015) - Maron, Martine; McAlpine, Clive A.; Watson, James E. M.; Maxwell, Sean; Barnard, Phoebe; Andersen, Alan
Abstract Aim Resource bottlenecks – periods of severe restriction in resource availability – triggered by increased climate variability represent important and little‐understood mechanisms through which climate change will affect biodiversity. In this review, we aim to synthesize the key global change processes that exacerbate the severity of bottlenecks in resource availability on animal populations, and outline how adaptation responses can help buffer the impacts. Location Global. Methods We collate examples from the literature of population‐level impacts of resource bottlenecks induced by extreme weather and climate events to explore the types of population impacts that have most frequently been recorded, and the type of extreme events associated with them. We then develop a conceptual framework that captures the factors contributing to species' vulnerability to climate‐induced spatial and temporal resource bottlenecks in increasingly variable environments. Results Increases in the frequency, severity and/or duration of extreme weather and climate events can trigger resource bottlenecks that act as powerful demographic constraints on terrestrial fauna, and often exacerbate other human‐induced pressures such as land use change. Such phenomena are likely to become more frequent and severe, with potentially nonlinear increases in impact. Forty‐nine instances of population‐level impacts from climate‐induced resource bottlenecks were recorded from the literature, including four extinctions and ten population crashes. Anthropogenic land use change interacts with increasing climatic variability to exacerbate these resource 'crunches', but can sometimes act as a buffer for species. Main Conclusions Resource bottlenecks are likely to be a large class of climate‐sensitive stressors whose impacts may play out at the population scale, even well within a species' apparent climatic envelope. More effective conservation responses to climate‐related threats include explicit actions, such as managing protected area networks for spatial and temporal resource complementarities, that buffer vulnerable species against bottlenecks.